The Relationship of Parenting Patterns with Toddlers Nutritional Status in Wailolong Village, East Nusa Tenggara - Molan, Veronika Nogo; Sinaga, Masrida; Riwu, Rut Rosina (Lontar : Journal of Community Health, 2023)
Toddlers are one of the groups at risk for nutritional problems. The intake of foods rich in nutrients has a good impact on the growth and development of children. Many factors influence the emergence of nutritional issues, including maternal parenting. This study aims to analyze the relationship of parenting with toddlers' nutritional status in Wailolong Village". This type of research is quantitative research with a cross-sectional research design. The sample consisted of 48 toddlers. Sampling in this study using a simple random sampling technique with a significance level of = 0.05. The results showed that there was a relationship between feeding patterns (p= 0.001), psychosocial stimulation (p= 0.019), hygiene practices (p= 0.022), and health care (p= 0.000) with the nutritional status of children under five. This study concludes a relationship between feeding patterns, psychosocial stimulation, hygiene practices, and health care and the nutritional status of children under five. It is expected that the Puskesmas health workers will provide information to mothers of toddlers about good feeding patterns based on the amount, type, and frequency of eating according to the needs of each age of the toddler and the attitude of the mother in giving love, paying attention, teaching toddlers about personal hygiene, and equipping them with personal hygiene cares about effective health promotion techniques to improve nutrition.